Diagnostic upper Gastrointestinal Endoscopy in Kaduna, Northwest Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:An upper gastrointestinal endoscopy (UGIE) is now a routine procedure and is a guide to the prevalence and nature of gastrointestinal tract diseases in an area.Aim:To report indications and findings for UGIE in a tertiary hospital in Kaduna, Nigeria, and compare with past reports in the region and from the rest of Nigeria and Africa.Settings and Design:A retrospective review of endoscopy records (2014–2021) of consecutive patients referred to the endoscopy unit of Barau Dikko Teaching Hospital, Kaduna, Nigeria.Statistical Analysis:The data were analyzed using IBM SPSS version 22.Results:Over seven years, 1,525 patients had diagnostic UGIE: mean age = 44.8 years (range 8–100), 61% ≥ 40 years, and 55.7% females. Dyspepsia (70%) and hematemesis/melena (14%) were the most common indications. Superficial gastritis (60%) was the most common endoscopic finding. Peptic ulcer disease (PUD) was diagnosed in 9.6% of patients: Gastric ulcer (6.6%) was more common than duodenal ulcer (3.6%) and more frequent in males than females (9.5% vs. 4.3%,P= 0.000) and in those ≥ 40 years compared with < 40 years (7.8% vs 5%,P= 0.032). Duodenal ulcer was also more common in males (6% vs 1.8%,P= 0.000). Erosive gastritis (20.5%), hiatus hernia (14.4%), esophagitis (13.7%), atrophic gastritis (8.3%), nodular gastritis (6.6%), esophageal varices (6.1%), and gastric carcinoma (1.2%) were other findings. There was no abnormality detected in 6% of patients.Conclusion:We reported a marked change in the pattern of some gastroduodenal diseases in our region. The patients are older and predominantly female. The prevalence of PUD has markedly declined with gastric ulcer now almost twice as common as duodenal ulcer.